Complexity in Global Health- Bridging Theory and Practice - Carlos A. Faerron Guzmán (Ubiquity Press, 2022)
Increasingly, health reflects an integrated outcome of a growing globalized system. Economic, political, cultural, environmental, and other global processes profoundly influence how we understand and approach health challenges. As these occur in a webbed, dynamic, and interdependent fashion, health can be viewed as a complex issue. Drawing from this understanding, in this viewpoint, I assert applying complexity theory to produce a definition of the field of global health. Complexity theory tenets such as non-linearity, transdisciplinarity, open-system analysis, and global-local phenomenology can provide a theoretical basis for a substantive understanding of global health phenomena and a richer instrumental approach to global health challenges. Harmonization between complexity theory and global health may provide the foundation to close the health equity gap put forth by the global health agenda.